OCORRÊNCIA DE PARASITÓIDES DA LARVA MINADORA DOS CITROS, PHYLLOCNISTIS CITRELLA STATION, NO MUNICÍPIO DE PRESIDENTE PRUDENTE, SP - Montes, S.m.n.m.; Boliani, A.c. [UNESP]; Papa, G. [UNESP]; Cerávolo, L.c.; Rossi, A.c.; Namekata, T. (Instituto Biológico, 2024)
The leafminer of citrus, Phyllocnistis citrella Station, is an important pest of Brazilian citriculture, because besides damages direct caused by its attack in the new leaves of the flush, has an important paper as approach agent to the citrus canker, due to the lesions that it caused in the leaves facilitating the entrance of the bacteria and its growth in the epiderms. The main objetive of this work went make the rising of the complex of native parasitoids of P. citrella and to verify the parasitism in field level in Estação de Pesquisas Biológicas, Presidente Prudente. They took place collections in an orchard of orange two years old, in a total of 105 plants, being collected 4 flushes/plant beweekly, of the 15 plants randomly. The collected material was maintained in BOD an 25±2ºC, 70±10% UR e 14 horas fotofase, conditioned into Petri fishers with paper filter humidified. After the emergency of the parasitoids, these were conserved in alcohol 70% and remeted for identification in the Federal University of São Carlos-UFSCAR. They were found three species, which were in decreasing order of frequency: Galeopsomyia sp., Elasmus sp. and Cirrospilus sp.

A larva minadora dos citros, Phyllocnistis citrella Station, é uma praga de grande importância na citricultura brasileira, pois além dos danos diretos causados pelo seu ataque nas folhas novas das brotações, tem um importante papel como agente disseminador do cancro cítrico, devido às lesões que provoca nas folhas facilitando a entrada da bactéria e seu crescimento na epiderme. O objetivo deste trabalho foi efetuar o levantamento do complexo de parasitóides nativos de P. citrella e verificar o parasitismo em nível de campo na Estação de Pesquisas Biológicas do Instituto Biológico, no Município de Presidente Prudente, SP. Realizaram-se coletas em um pomar de laranja Pêra de 2 anos de idade, num total de 105 plantas, sendo coletados 4 ponteiros/planta quinzenalmente, de 15 plantas ao acaso. O material coletado foi mantido em BOD a 25 ± 2ºC, U.R. 70 ± 10% e fotofase de 14 horas, acondicionado em placas de Petri com papel de filtro umedecido. Após a emergência dos parasitóides, estes foram conservados em álcool 70% e enviados para identificação na Universidade Federal de São Carlos. Foram encontradas 3 espécies de parasitóides, os quais, em ordem decrescente de frequência foram: Galeopsomyia sp. (52,83%), Elasmus sp. (37,74%) e Cirrospilus sp. (9,43%).
Keywords: Phyllocnistis citrella; citrus; parasitoids; occurrence.; Phyllocnistis citrella; citros; parasitóides; ocorrência.